Patient experiences in primary care do not differ according to rurality: a cross-sectional study - Makoto Kaneko; Hironori Yamada; Tadao Okada (BMC Primary Care)
Abstract Background Living in rural areas is a major contributor of health inequity. Tackling health inequity is important for primary care physicians. Therefore, it is important to compare the quality of primary care between rural and urban areas. To the best of our knowledge, this is the first study to examine the association between rurality and patient experience (PX) in Japan using validated measures. Methods This cross-sectional study was conducted using online surveys. Participants were selected using a stratified random sample based on sex and age. The Japanese version of the Person-Centered Primary Care Measure (PCPCM) was used as an indicator of PX. We used the Rurality Index for Japan (RIJ) to measure rurality. Furthermore, we used multivariate linear regression analysis to examine the relationship between the RIJ and PCPCM after adjusting for confounders. Results Of the 1112 eligible participants, 800 responded to the survey (response rate:71.9%). The mean PCPCM scores were 2.46 (standard deviation: 0.73) and median RIJ was 15 (interquartile range: 6–33). The crude and adjusted coefficients of rurality were − 0.02 (− 0.006–0.001, p = 0.114) and − 0.02 (− 0.005–0.001), respectively, demonstrating that rurality was not significantly associated with the total PCPCM score. Subgroup analyses were similar to the main analyses. Conclusion We found that PX in primary care did not differ by rurality in the general Japanese population.